Economics and Ageing Volume II: Policy and Applied - Iparraguirre, José Luis (Springer International Publishing, 2018)
This upper level textbook provides a coherent introduction to the economic implications of individual and population ageing. Placing economic considerations into a wider social sciences context, this is ideal reading not only for advanced undergraduate and masters students in economics, health economics and the economics of ageing, but also policy makers, students, professionals and practitioners in gerontology, sociology, health-related sciences and social care. This volume discusses the fiscal implications of ageing, health economics and long-term care. Fiscal policy issues include generational accounting and national transfer accounts, the relationship between ageing, public expenditure and fiscal policy, the age profiles of public expenditures and taxes, and the relationship between ageing, capital and labour taxation. Health economics with regard to ageing comprises healthy and disability-free life expectancy, the relationship between health inequalities and age, the macroeconomic implications of population health, the socio-economic determinants of health, the interaction between ageing and both individual and aggregate health expenditure, and economic approaches to valuing later life. This volume closes with an exposition of the economics of formal and informal care, as well as questions around insurance, risk and the so-called `sandwich generation'. José Luis Iparraguirre is Chief Economist at Age UK and Professor of Economics at the University of Morón, Buenos Aires, Argentina. .